URGENSI METODE PEMBELAJARAN INDUKTIF DALAM UPAYA PENINGKATAN KEMAMPUAN INTELEKTUAL SISWA - Aviv, Sholeh; Alaydrus, Muhammad Firza (Jurnal al Hikmah, 2018)
Inductive learning method is one of the methods used by some teachers to deliver the material to the students. This method is pointed out as a method that is able to increase intellectual students with ekseleratif. For that reason, the role of teachers in an effort to improve the intellectual students is very important. So the teachers are required to improve the learning method, especially this inductive learning method. This study aims to describe the form of inductive learning method in the learning process, want to describe the intellectual development effort of the students and want to describe the urgency of inductive learning in the process of intellectual development of students After the researchers attempted to conduct research on the urgency of inductive learning methods for the intellectual development of students, it turns out researchers found, that the inductive learning method has a significant urgent in an effort to develop intellectual students